2021
DOI: 10.1055/a-1705-0921
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and adverse events of endoscopic clipping versus band ligation for colonic diverticular hemorrhage: a large-scale multicenter cohort study

Abstract: Background and study aims: Prior studies have shown the effectiveness of endoscopic band ligation (EBL) and clipping for colonic diverticular hemorrhage (CDH) but have been small and conducted at single centers. Thus, we investigated which was the more effective and safe treatment in a multicenter long-term cohort study. Patients and methods: We reviewed data for 1,679 patients with CDH who were treated with EBL (n=638) or clipping (n=1,041) between January 2010 and December 2019 at 49 hospitals across Japan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The guidelines recommend endoscopic clipping for CDB because it is the most common treatment and typically poses a lower risk of tissue injury 1,23 . However, endoscopic band ligation has been shown to be ultimately superior to endoscopic clipping regarding short‐term and long‐term rebleeding rates and the need for IVR/surgery in CDB cases 34,35 . We performed endoscopic band ligation in 83% (124/149) of patients with definitive CDB (Table S1), which contributed to the risk reduction of 30‐day rebleeding in the recent bleeding group (Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines recommend endoscopic clipping for CDB because it is the most common treatment and typically poses a lower risk of tissue injury 1,23 . However, endoscopic band ligation has been shown to be ultimately superior to endoscopic clipping regarding short‐term and long‐term rebleeding rates and the need for IVR/surgery in CDB cases 34,35 . We performed endoscopic band ligation in 83% (124/149) of patients with definitive CDB (Table S1), which contributed to the risk reduction of 30‐day rebleeding in the recent bleeding group (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…1,23 However, endoscopic band ligation has been shown to be ultimately superior to endoscopic clipping regarding short-term and long-term rebleeding rates and the need for IVR/surgery in CDB cases. 34,35 We performed endoscopic band Candidates for early colonoscopy ligation in 83% (124/149) of patients with definitive CDB (Table S1), which contributed to the risk reduction of 30-day rebleeding in the recent bleeding group (Table S2). However, the impact of clipping accompanied by early colonoscopy should be investigated by accumulating a larger number of cases in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Giri and Sundaram for their interest in our study and for their comments. In this study, we reviewed data for 1679 patients with colonic diverticular hemorrhage (CDH) who were treated with endoscopic band ligation (EBL) or clipping at 49 hospitals across Japan (CODE BLUE-J study), and the association between endoscopic treatment and clinical outcomes was analyzed using logistic regression models [1]. The treatment strategy was chosen at the discretion of each hospital and endoscopist.…”
Section: Reply To Drs Giri and Sundarammentioning
confidence: 99%
“…
In their recent article, Kobayashi et al [1] analyzed the retrospective multicenter data from the CODE BLUE-J trial and reported higher efficacy of endoscopic band ligation (EBL) in colonic diverticular hemorrhage (CDH) compared with endoscopic clipping. EBL was associated with significantly lower early and late rebleeding rates, ultimately reducing the need for interventional radiology.
…”
mentioning
confidence: 99%